The Gut and the Translocated Microbiomes in HIV Infection: Current Concepts and Future Avenues - Nganou-Makamdop, Krystelle; Douek, Daniel C. (Pathogens and Immunity, 2024)
It is widely acknowledged that HIV infection results in disruption of the gut’s mucosal integrity partly due a profound loss of gastrointestinal CD4+ T cells that are targets of the virus. In addition, systemic inflammation and immune activation that drive disease pathogenesis are reduced but not normalized by antiretroviral therapy (ART). It has long been postulated that through the process of microbial translocation, the gut microbiome acts as a key driver of systemic inflammation and immune recovery in HIV infection. As such, many studies have aimed at characterizing the gut microbiota in order to unravel its influence in people with HIV and have reported an association between various bacterial taxa and inflammation. This review assesses both contra dictory and consistent findings among several studies in order to clarify the overall mechanisms by which the gut microbiota in adults may influence immune recovery in HIV infection. Independently of the gut microbiome, observations made from analysis of microbial products in the blood provide direct insight into how the translocated microbiome may drive immune recovery. To help better understand strengths and limitations of the findings reported, this review also highlights the numerous factors that can influence microbiome studies, be they experimental methodologies, and host-intrinsic or host-extrinsic factors. Altogether, a fuller understanding of the interplay between the gut microbiome and immunity in HIV infection may contribute to preventive and therapeutic approaches.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Gut microbiome; HIV; Immune recovery; Inflammation; Microbial translocation; Translocated microbiome